PERSEPSI AUDITOR INTERNAL TERHADAP PENANGANAN FRAUD YANG TERJADI DI PERUSAHAAN - Pradita, Hendik; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the perception of internal auditor to the fraud management which has occurred at PT. Penerbit Erlangga Mahameru and to find out the ways which have been used by internal auditors in disclosuring of fraud that has occurred in the company. To investigate the employee performance particularly the marketing department in order to achieve the effective and efficient performance.This research uses descriptive research which has been conducted at PT. Penerbit Erlangga Mahameru. The research subject is corporate internal auditor. The research object is auditor perception to the fraud management which has occurred in the company. The data collection technique has been conducted by using qualitative analysis with the secondary and primary data.The result of this research shows that the perception of internal auditors give significant influence to the fraud management. It is shown by the obedience of marketing employee to the systems and procedures when the internal auditors often conducted the investigation and publish the result of audit. The procedure which can be carried out by the internal auditor is to maximize the visitation to the outside regions such as out of towns / islands to conduct examination to the customer balances and increase the numbers of employees of internal audit in order to perform evenly control / traffic.Keywords: Internal Audit, fraud, performance.